Consultation diagnoses and procedures billed among recent graduates practicing general otolaryngology – head & neck surgery in Ontario, Canada - Antoine Eskander; Paolo Campisi; Ian J. Witterick; David D. Pothier (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background An analysis of the scope of practice of recent Otolaryngology – Head and Neck Surgery (OHNS) graduates working as general otolaryngologists has not been previously performed. As Canadian OHNS residency programs implement competency-based training strategies, this data may be used to align residency curricula with the clinical and surgical practice of recent graduates. Methods Ontario billing data were used to identify the most common diagnostic and procedure codes used by general otolaryngologists issued a billing number between 2006 and 2012. The codes were categorized by OHNS subspecialty. Practitioners with a narrow range of procedure codes or a high rate of complex procedure codes, were deemed subspecialists and therefore excluded. Results There were 108 recent graduates in a general practice identified. The most common diagnostic codes assigned to consultation billings were categorized as ‘otology’ (42%), ‘general otolaryngology’ (35%), ‘rhinology’ (17%) and ‘head and neck’ (4%). The most common procedure codes were categorized as ‘general otolaryngology’ (45%), ‘otology’ (23%), ‘head and neck’ (13%) and ‘rhinology’ (9%). The top 5 procedures were nasolaryngoscopy, ear microdebridement, myringotomy with insertion of ventilation tube, tonsillectomy, and turbinate reduction. Although otology encompassed a large proportion of procedures billed, tympanoplasty and mastoidectomy were surprisingly uncommon. Conclusion This is the first study to analyze the nature of the clinical and surgical cases managed by recent OHNS graduates. The findings demonstrated a prominent representation of ‘otology’, ‘general’ and ‘rhinology’ based consultation diagnoses and procedures. The data derived from the study needs to be considered as residency curricula are modified to satisfy competency-based requirements.